La Biennale di Venezia; 49. esposizione internazionale d'arte : Platea dell'umanita - La Biennale di Venezia Venice; La Biennale di Venezia 2001 Venice 10/06-04/11/2001; Szeeman, Harald; Liveriero Lavelli, Cecilia (Milano : Electa, 2001)
A1 - 53167 ; Akerman, Chantal ; Akpan, Sunday Jack ; Alÿs, Francis ; Ang Tiong ; Anur ; Artigas, Gustavo ; Atelier van Lieshout ; Baldessari, John ; Bartolini, Massimo ; Beckett, Samuel ; Beecroft, Vanessa ; Beuys, Joseph ; Billingham, Richard ; Bismuth, Pierre ; Bödecker, Erich ; Bonvicini, Monica ; Botto & Bruno ; Bourgeois, Louise ; Bruch, Martin ; Bruguera, Tania ; Brus, Günter ; Buchanan, Roderick ; Burden, Chris ; Cai Guo-Qiang ; Camara, Seni ; Cattelan, Maurizio ; Cecchini, Loris ; Chen Zhen ; Com & Com ; Cracking Art ; Cunningham ; D'Andrea, Raffaelo ; Dabernig, Josef ; Dago Ousmane Ndiaye ; Dean, Max ; Devlin, Lucinda ; Dijkstra, Rineke ; Do-Ho, Suh ; Douglas, Stan ; Egoyan, Atom ; Eliasson, Olafur ; Extra Territoria ; Federle, Helmut ; Galindo, Regina ; Garcia Rodero, Cristina ; Geiger, Markus ; Gerz, Jochen ; Gianikian, Yervant ; Goba, John ; Gonzalez Plama, Luis ; Graham, Paul ; Granö, Veli ; Green, Renée ; Hai Bo ; Herrero, Federico ; Hill, Gary ; Horelli, Laura ; James, Todd ; Jelmorini, Ettore ; Jusidman, Yishai ; Kabakov, Ilya ; Kabakov, Ilya & Emilia ; Karmitz, Marin ; Kiarostami, Abbas ; Kleinberg, Susan ; Kosuth, Joseph ; Land, Peter ; Laurette, Matthieu ; Lehanka, Marko ; van Lieshout, Joep ; Löhr, Christiane ; Lum, Ken ; Lüscher, Ingeborg ; Manders, Mark ; Manninen, Tuomo ; Margreiter, Dorit ; Marisaldi, Eva ; Maruscenko, Viktor ; McCarthy, Paul ; McGee, Barry ; Merz, Marisa ; Michel, Chantal ; Monge, Priscilla ; Mueck, Ron ; Mwai, Cheff ; Neri, Marco ; Neto, Ernesto ; Ngnetchopa, Jean-Baptiste ; Nicolai, Carsten ; Nicolai, Olaf ; Nuez, Gilberto De La ; Ocampo, Manuel ; Odermatt, Arnold ; Onofre, João ; Orimoto Tatsumi ; Ostojic, Tanja ; Pernice, Manfred ; Pfeiffer, Paul ; Pilson, John ; Powers, Stephen ; Prince, Richard ; etc.
Engelse tekst
boek